Catalysing innovation: Infusing entrepreneurial skills into science learning in Eswatini’s selected secondary schools - Tabetha N. Pazvakavambwa; Pinias Chikuvadze; Claretah Makuvire; Young Mudavanhu (Eureka: Journal of Educational Research, 2025)
Despite increasing global stress on education that nurtures innovation and empowerment, Science, Technology, Engineering, and Mathematics (STEM) curricula remain largely disengaged from entrepreneurial settings. This study explores the infusion of entrepreneurial skills into science learning to catalyse innovation in Eswatini’s selected secondary schools. Anchored in a mixed-methods approach, this study collected data through questionnaires, interviews, and literature methods. Through the use of a comparative matrix, results from the reviewed literature were triangulated with questionnaire data and qualitative responses by aligning developing themes. The stratified random sampling technique was used to select 30 respondents. Quantitative data were analysed using descriptive statistics, qualitative responses underwent thematic analysis, and literature data were analysed through systematic content analysis. Results revealed a high level of awareness among teachers regarding the importance of entrepreneurial skills in science learning. Additionally, respondents reported employing innovative pedagogical strategies, including inquiry-based and project-based learning, to promote entrepreneurship-oriented instruction. The study highlighted the necessity for strategic policy reforms and sustained professional development to equip science teachers with the requisite skills and support. It advocates for the creation of collaborative, interdisciplinary learning environments that nurture both scientific inquiry and entrepreneurial thinking. Ultimately, the research concludes that entrepreneurial skills are being infused into science learning to a considerable extent to catalyse innovation. This study advances STEM education reform by integrating entrepreneurial skills into Eswatini’s science curriculum. The results offer valuable insights for policymakers, teachers, and curriculum developers seeking to align science learning with the national innovation and economic development agenda.